Pendekatan real-life untuk meningkatkan kemampuan menyimak bahasa Indonesia bagi penutur asing - Ida Widia; Robita Ika Annisa (Jurnal Bahasa Indonesia bagi Penutur Asing, 2023)
This article explores the BIPA (Indonesian as a foreign language) learners’ competency in listening conversations using a real-life approach. This is based on the background that mastering a foreign language, especially listening in real-life conversation, is difficult even though they have learned the language. To address these issues, a real-life approach was adopted to train the BIPA students to listen to the conversations in a real-world setting. This study uses the qualitative descriptive method to investigate how using a real-life approach can aid BIPA learners in developing their listening abilities. BIPA students from India, Japan, Austria, and South Korea were included as a sample in this study. As a result, the appearance of other sound variants in real-life conversation turns out to become an aspect to distract them from listening. In addition, students frequently imitate pronunciation and pick up vocabulary from the literature and environment they are listening to. Therefore, the real-life approach helps the BIPA students to have a better understanding of listening in real-world conversations. Additionally, students can distinguish between different sound variants and pinpoint the purpose of their listening.